FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA DENGAN PERSEPSI PENDAPATAN SEBAGAI VARIABEL MODERATING (STUDI KASUS PADA MAHASISWA FEB UNARS SITUBONDO) - Alifayosi Faorika; Ediyanto Ediyanto; Rini Kartika Sari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of this study is to determine the Factors Influencing Student Entrepreneurial Interest with Perception of Income as a Moderating Variable (Case Study on FEB UNARS Situbondo Students). The sampling technique used in this study was simple random sampling of 77 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the study indicate that Entrepreneurship education has a negative but significant effect on Entrepreneurial Interest, Self-efficacy has a negative and insignificant effect on Entrepreneurial Interest. Perception of income significantly becomes a moderating variable for the influence of Entrepreneurship Education on Entrepreneurial Interest Perception of income significantly becomes a moderating variable for the influence of Self-efficacy on Entrepreneurial Interest.